Improvement of Skills for Preparing Electronic Teaching Materials (E-Modules) in the Form of Flipped Books for Sociology Anthropology Teachers at High Schools in Sukoharjo Regency - Ghufronudin, Ghufronudin; Narendra , Bagas; Astutik, Dwi (Prospect: Jurnal Pemberdayaan Masyarakat, 2023)
In the era of disruption of the industrial revolution 4.0, the intervention of digital technology has had a huge impact on human life. Especially in the field of education, the presence of digital technology can contribute more to the implementation of online learning at all levels of education. This service is designed with the aim of providing knowledge and skills through collaborative preparation of electronic teaching materials (e-modules) for Sociology Anthropology teachers who are members of the Sociology MGMP Sukoharjo Regency. This service activity is carried out in three stages, namely discussions about teaching materials, practical facilities and direct assistance as well as reflection and evaluation of implementation. The results of this activity showed that participants felt practical benefits in the form of knowledge and skills in compiling and developing electronic teaching materials by presenting interesting, innovative and creative material content to improve the quality of teacher learning both online and offline.